Well-being effects of self-employment: A spatial inquiry - Maria Abreu; Özge Öner; Aleid Elizabeth Brouwer; Eveline van Leeuwen (Research Institute of Industrial Economics (IFN), 2018)
Our paper presents an empirical analysis of entrepreneurial well-being using a large-scale longitudinal household survey from the UK that tracks almost 50,000 individuals across seven waves over the period 2009-2017, as well as a number of exploratory case studies. We contribute to the existing literature by investigating how entrepreneurial well-being varies across locations along the urban-rural continuum, and across wealthy-deprived neighbourhoods. We use a Coarsened Exact Matching (CEM) approach to compare the well-being outcomes of individuals who switch into self-employment from waged employment, and show that entrepreneurial well-being, in the form of job satisfaction, is significantly higher for those living in semi-urban locations, relative to those living in urban and rural locations. We argue that semi-urban locations provide an optimal combination of ease of doing business and quality of life. Our results also show that individuals in wealthy neighbourhoods who switch into self-employment experience higher job satisfaction than otherwise comparable individuals living in materially deprived neighbourhoods, although the latter experience greater levels of life satisfaction following the switch.
Keywords: E24; I13; L26; P25; R20; R23; 330; Entrepreneurship; Well-being; Self-employment; Urban-rural; Neighbourhood effects